What should services for people with autism look like?. Issue 1 (30th July 2015) - Povey, Carol
Abstract : Purpose: – The purpose of this paper is to examine the key components and approaches which contribute to good autism services. Design/methodology/approach: – This paper reviews some of the literature around quality of life in autism services and describes the approach taken by The National Autistic Society. Findings: – There is minimal research to enable service providers to shape their services according to what is most important for people with autism. The SPELL framework used by The National Autistic Society provides an approach which can be adapted to individual needs. Good autism services need to be based on a sound and practical understanding of autism. Practical implications: – People on the autism spectrum should be involved in determining what outcomes are most important to them, and services should then be based around those needs. Services therefore need to be individualised and person centred, underpinned by an in-depth knowledge and understanding of autism. Originality/value: – This review highlights the importance of people being involved in determining what is important to them and how services which support them should be shaped and delivered.